Kedudukan Hukum Ahli Waris Penyandang Cacat Mental Dalam Memperoleh Hak Warisnya (Harta Waris) - Imam Sanusi; Dominikus Rato; Dyah Octhorina Susanti (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2023)
Every human being is born with their own diversity and uniqueness, some have differences called special needs. Many people out there view that a person who is born with special needs is called an imperfect human or is commonly called a cripple. Normative legal research is used in this study to find solutions to the legal position of heirs of people with mental disabilities. The approach used is a statutory approach and a conceptual approach to the authority of guardians, inheritance management, and the rights of people with mental disabilities. People who have mental disorders or disabilities when faced with legal problems, in this case regarding the matter of inheritance, they cannot take/perform legal actions themselves. Even though he is in a state of being unable to carry out legal actions independently, he is still referred to as a legal subject. By recognizing persons with mental disabilities as legal subjects, they are included in legal subjects who are incompetent and can be assisted by guardians to receive inheritance. Keywords : Inheritance, Mental Disability, Empowerment